Regulation of Central Nervous System Myelination in Higher Brain Functions - Mara Nickel; Chen Gu (Neural Plasticity)
The hippocampus and the prefrontal cortex are interconnected brain regions, playing central roles in higher brain functions, including learning and memory, planning complex cognitive behavior, and moderating social behavior. The axons in these regions continue to be myelinated into adulthood in humans, which coincides with maturation of personality and decision-making. Myelin consists of dense layers of lipid membranes wrapping around the axons to provide electrical insulation and trophic support and can profoundly affect neural circuit computation. Recent studies have revealed that long-lasting changes of myelination can be induced in these brain regions by experience, such as social isolation, stress, and alcohol abuse, as well as by neurological and psychiatric abnormalities. However, the mechanism and function of these changes remain poorly understood. Myelin regulation represents a new form of neural plasticity. Some progress has been made to provide new mechanistic insights into activity-independent and activity-dependent regulations of myelination in different experimental systems. More extensive investigations are needed in this important but underexplored research field, in order to shed light on how higher brain functions and myelination interplay in the hippocampus and prefrontal cortex.